2017
DOI: 10.1016/j.artd.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

ESR and CRP are useful between stages of 2-stage revision for periprosthetic joint infection

Abstract: BackgroundSerum erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are important tests in the initial diagnosis of periprosthetic joint infection. Many surgeons also use these tests to determine if infection has resolved between stages of a 2-stage procedure, but little data exist regarding this practice.MethodsA retrospective review of our institutional total joint databases was conducted to determine sensitivity, specificity, and predictive values of elevated ESR and/or CRP to diagnose persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
2
16
1
Order By: Relevance
“…However, the plasma D-dimer was inferior to fibrinogen. Nevertheless, compared with the previous studies of serum CRP and ESR reported before reimplantation, plasma D-dimer seems to be a better diagnostic indicator [33,34].…”
Section: Discussioncontrasting
confidence: 67%
“…However, the plasma D-dimer was inferior to fibrinogen. Nevertheless, compared with the previous studies of serum CRP and ESR reported before reimplantation, plasma D-dimer seems to be a better diagnostic indicator [33,34].…”
Section: Discussioncontrasting
confidence: 67%
“…In their small case series, Lindsay et al [14] We found that the preexplantation ESR was significantly higher in PJI caused by resistant versus nonresistant bacteria. This is not necessarily surprising given the virulence of MRSA compared with nonresistant bacteria.…”
Section: Discussionmentioning
confidence: 67%
“…We found that both the DESR and DCRP percentages were poor markers of recurrent or persistent infection risk. Several previous studies have investigated how to best monitor infection status using serologic testing in the period before reimplantation [10,13,14,25]. However, all studies of this nature suffer from the fact that two-stage reimplantation is a relatively successful procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma D-dimer was observed to have a lower sensitivity and specificity than fibrinogen (83.3% and 41.9% vs. 87.5% and 62.8%, respectively); however, it was inferior to fibrinogen. Nevertheless, compared with previous studies on serum CRP and ESR before reimplantation, plasma D-dimer appears to be a better diagnostic indicator [34,35]. The first serum D-dimer study performed by Shahi and co-workers also found that the two cases of failed second stage replacement caused by reinfection had increased D-dimer levels before reimplantation surgery, while serum CRP and ESR levels were normal [13].…”
Section: Discussionmentioning
confidence: 78%